2001
DOI: 10.1097/00007691-200104000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Tacrolimus and Cyclosporine on the Pharmacokinetics of Mycophenolic Acid

Abstract: Mycophenolate mofetil (MMF) is almost completely absorbed from the gut and is rapidly de-esterified into its active drug, mycophenolic acid (MPA). The main metabolite is glucuronidated MPA (MPAG), which is excreted into bile and undergoes enterohepatic recirculation. Studies in healthy volunteers treated with cholestyramine show that interruption of the enterohepatic recirculation decreases MPA exposure by approximately 40%. Published data show a difference in mycophenolic acid plasma concentrations between ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
188
1
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(207 citation statements)
references
References 32 publications
13
188
1
5
Order By: Relevance
“…23 Two possibilities have been suggested to underlie these drug interactions: (1) Tac augments the bioavailability of MMF through inhibition of MPA glucuronidation, the primary metabolic pathway for MPA 26 ; and (2) CsA inhibits enterohepatic recycling of MPA. 27 Our additional studies on the pharmacokinetics of mycophenolate glucuronide suggest both these mechanisms may apply and are reported elsewhere. 28 These drug interactions have definite implications for patients because conversion from comedication with CsA to Tac could result in a sudden increase in MPA levels and potential toxicity.…”
Section: Discussionmentioning
confidence: 70%
“…23 Two possibilities have been suggested to underlie these drug interactions: (1) Tac augments the bioavailability of MMF through inhibition of MPA glucuronidation, the primary metabolic pathway for MPA 26 ; and (2) CsA inhibits enterohepatic recycling of MPA. 27 Our additional studies on the pharmacokinetics of mycophenolate glucuronide suggest both these mechanisms may apply and are reported elsewhere. 28 These drug interactions have definite implications for patients because conversion from comedication with CsA to Tac could result in a sudden increase in MPA levels and potential toxicity.…”
Section: Discussionmentioning
confidence: 70%
“…We selected higher doses of MMF in view of several publications that showed that MMF had lower mycophenolic acid concentration levels when combined with CsA. 11,27 Recent findings from animal model studies have also supported the suggestion that mycophenolic acid levels were lower in allo-HSCT than in solid-organ transplantation. 28 Furthermore, pharmacokinetic assays of mycophenolic acid have shown a higher therapeutic area under the curve at a dosage of 3 g daily in unrelated donor allo-RIC.…”
Section: Discussionmentioning
confidence: 94%
“…Plasma MPA concentrations are influenced by renal graft function [4][5][6], serum albumin binding and concentration [6,7], liver function [4,8] and haemoglobin concentrations [6]. MPA is also subject to pharmacokinetic drug interactions with calcineurin inhibitors and mTOR inhibitors [9][10][11]. Other drugs can also influence the pharmacokinetics of MPA through interaction with the UDP-glucuronosyltransferases (UGTs) or the organic anion transporter MRP2 [1,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%